ANCAMAN RADIKALISME DALAM TATA KELOLA KEBIJAKAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI KABUPATEN JEMBER - Ningtyas, Binaridha Kusuma; Sulistyono, Sulistyono; Fauziyah, Fauziyah (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2025)
This article aims to identify challenges in the protection policy for Indonesian migrant workers from Jember Regency with a focus on the threat of radicalization in the digital era. The development of information technology and global migration affects various aspects of migrant workers lives, not only in the economic aspect, but also has the potential to open up opportunities for radicalism. This research uses descriptive qualitative methods, with data collection through interviews and study of related documents. The research results show that disinformation circulating on social media, as well as Indonesian migrant workers social isolation abroad, are factors that exacerbate vulnerability to radicalism. Social media is the main channel for job information, but it often carries the risk of fraud and recruitment by illegal agents. Apart from that, the extremism-based violence faced by Indonesian migrant workers also appears as a threat that has not received much attention. This research suggests the need to strengthen Indonesian migrant workers protection policies, especially in utilizing technology and increasing digital literacy to prevent radicalization among Indonesian migrant workers.